The Compilation of Islamic Law: Foundations, Structure, and Prospects for Legal Transformation - Ronaldi; Zulpandri; Syaifullah; Desi Asmaret; Julhadi; Hamdan Chehdimae (Walidem Institute and Publishing, 2025)
Objective: This study aims to examine the history of the birth of the Compilation of Islamic Law (CIL), analyze its position in the national legal system, and evaluate the opportunities and challenges in changing its status from Presidential Instruction to Law. Theoretical framework: The theoretical framework used is the theory of the hierarchy of legal norms based on Law No. 12 of 2011, which explains the level of legal force in the legal system. The fiqh siyasah approach is also used to understand the position of Islamic law in the context of the modern state. Literature review: CIL is a codification of Islamic law that unites the diversity of sects in the practice of religious justice. Although functional has been widely used since 1991, its status as a Presidential Instruction makes its legal force weak. Many parties support the upgrade of its status to have stronger legitimacy. Methods: This research uses a qualitative approach with a literature study method. Data is obtained from relevant legal documents, academic literature, and laws and regulations. The analysis was carried out in a descriptive-analytical manner to answer the problems studied. Results: The results show that although CIL is the main reference in religious courts, its status as a Presidential Instruction outside the hierarchy of the law causes legal uncertainty. Therefore, the change in status to a law is considered important to strengthen its legality and effectiveness in the national legal system. Implications: Upgrading the status of CIL to law will strengthen legal certainty, increase democratic legitimacy, and open up space for Islamic law reform that is relevant to the social conditions of Indonesian society. Novelty: This research offers a new approach by emphasizing the importance of juridical and legal politics in strengthening CIL. Different from the previous study, the focus of this study is on the urgency of CIL legislation to strengthen the position of formal Islamic law in Indonesia.